Mathematical difficulties encountered by physics students in kinematics : a case study of form 4 classes in a high school in Botswana - Moyo, Ndumiso Michael (Stellenbosch : Stellenbosch University, 2020)
Thesis (MPhil)--Stellenbosch University, 2020.